Urine Biomarkers Combined With Ultrasound for the Diagnosis of Obstruction in Pediatric Hydronephrosis - Kazlauskas, Vytis; Bilius, Vytautas; Jakutis, Virginijus; Komiagiene, Renata; Burnyte, Birute; Verkauskas, Gilvydas (Frontiers in Pediatrics, 2022)
INTRODUCTION To establish the efficacy of ultrasound (US) combined with urine biomarkers in differentiating patients who require surgical management from those who do not, avoiding invasive investigations. MATERIALS AND METHODS: From February 2019 to February 2021, all pediatric patients who presented with hydronephrosis were selected for the study. All renal units (RU) were evaluated by US and fresh frozen voided urine samples were collected at the time of inclusion. Hydronephrosis grade was evaluated by society for fetal urology (SFU) and alternative grading system (AGS). Patients who had high grade hydronephrosis on US were referred to renal scan (RS) or intervention, when there was an increase of dilatation in subsequent follow-up images. Fresh frozen urine from control group with no history of renal diseases and no renal anomalies on US was collected. We compared differences of US parameters combined with urine biomarkers between surgically and non-surgically managed patients and between the groups of patients when they were stratified by different RS findings and analyzed whether urinary biomarkers give any additional value to US. Instead of anterior-posterior diameter (APD) we used its ratio with mid-parenchymal thickness. The additional efficacy of biomarkers to US was calculated when US component was derived to a cumulative APD/mid-parenchymal ratio. RESULTS 64 patients with hydronephrosis were prospectively included in the study accounting a total of 81 patient visits and 162 RUs evaluated. A control group of 26 patients was collected. Mean age at inclusion in hydronephrosis group was 43.7(±45.5) months and a mean age in a control group was 61.2(±41.3) months. Cumulative APD/mid-parenchymal ratio combined with urinary albumin, β2 microglobulin (β2-M) and urinary Neutrophil Gelatinase-Associated Lipocalcin may have a better performance in prediction of surgical intervention than cumulative APD/mid-parenchymal ratio alone (p=0.1). The best performance to detect increased tissue transit time and obstructive curve on RS was demonstrated by β2-M creatinine ratio. Increased cumulative APD/mid-parenchymal ratio with biomarkers together had a fair good sensitivity and specificity for detection of DRF <40 %. CONCLUSIONS According to our data APD/mid-parenchymal ratio alone has good efficacy in prediction of surgery and abnormal RS findings especially when combined with urine biomarkers.